COMPARATIVE STUDY OF LEARNING RESULTS TO DRAW PERSPECTIVE USING CULTURAL AND CONVENTIONAL PEER TEACHERS LEARNING METHODS - Indra Mawan Sitepu; Sugito Sugito (Melayu Arts and Performance Journal, 2021)
This study aims to prove the comparison of student learning outcomes in perspective drawing using peer tutoring and conventional learning methods. The population in this study were all works of students of class X IPA (3 classes) and students of class X IPS (3 classes) and the research sample was 36 students or 72 works. In this sample, two stages of action were given, namely initial sampling with the teaching and learning process using conventional learning methods. Based on the results of the study, the first test score average was 71.43 and the second test score was 82.74. The results of the mean difference test show that the average of the second value is better than the first value. Based on the results of hypothesis testing with a significance of α = 0.5 with dk 70 obtained t table = 1.6669. So the results of hypothesis testing obtained tcount 5.52> ttable 1.6669. So Ha is accepted as well as rejected by Ho, then the conclusion is that there are significant differences in the work of perspective drawing with the peer tutor learning method.Keywords: Learning Methods ; Learning Outcomes.AbstrakPenelitian ini bertujuan untuk membuktikan perbandingan hasil belajar peserta didik dalam  menggambar perspektif menggunakan metode pembelajaran tutor sebaya dan konvensional. Populasi dalam penelitian ini adalah seluruh karya peserta didik  kelas X IPA (3 kelas) dan peserta didik  kelas X IPS (3 kelas) dan diperoleh  sampel  penelitian  yaitu  sebanyak 36 peserta didik atau 72 karya. Pada sampel ini diberi dua tahap tindakan yaitu pengambilan sampel awal dengan proses belajar-mengajar menggunakan metode pembelajaran konvensional. Berdasarkan  hasil  penelitian  diperoleh  rata-rata  nilai tes pertama sebesar 71,43 dan nilai tes kedua 82,74. Hasil uji perbedaan  rata-rata  menunjukkan bahwa rata-rata nilai kedua lebih baik dari pada nilai pertama. Berdasarkan hasil uji hipotesis dengan signifikansi α = 0,5 dengan dk 70 didapat ttabel = 1,6669. Jadi hasil uji hipotesis diperoleh thitung 5,52 > ttabel 1,6669. Jadi Ha diterima sekaligus ditolak Ho kemudian kesimpulannya adalah terdapat perbedaan yang signifikan pada hasil karya menggambar perspektif dengan metode pembelajaran tutor sebaya.Kata Kunci: Metode Pembelajaran, Hasil Belajar.